Environmentally Regulated Glycosome Protein Composition in the African Trypanosome - Bauer, Sarah (American Society for Microbiology, 2013)
Trypanosomes compartmentalize many metabolic enzymes in glycosomes, peroxisome-related microbodies that are essential to parasite survival. While it is understood that these dynamic organelles undergo profound changes in protein composition throughout life cycle differentiation, the adaptations that occur in response to changes in environmental conditions are less appreciated. We have adopted a fluorescent-organelle reporter system in procyclic Trypanosoma brucei by expressing a fluorescent protein (FP) fused to a glycosomal targeting sequence (peroxisome-targeting sequence 2 [PTS2]). In these cell lines, PTS2-FP is localized within import-competent glycosomes, and organelle composition can be analyzed by microscopy and flow cytometry. Using this reporter system, we have characterized parasite populations that differ in their glycosome composition. In glucose-rich medium, two parasite populations are observed; one population harbors glycosomes bearing the full repertoire of glycosome proteins, while the other parasite population contains glycosomes that lack the usual glycosome-resident proteins but do contain the glycosome membrane protein TbPEX11. Interestingly, these cells lack TbPEX13, a protein essential for the import of proteins into the glycosome. This bimodal distribution is lost in low-glucose medium. Furthermore, we have demonstrated that changes in environmental conditions trigger changes in glycosome protein composition. These findings demonstrate a level of procyclic glycosome diversity heretofore unappreciated and offer a system by which glycosome dynamics can be studied in live cells. This work adds to our growing understanding of how the regulation of glycosome composition relates to environmental sensing.